A study of the semantic preference and semantic prosody associated with the denominations of aging people - Jamet, Denis; Coupé, Christophe (Journal of Language and Aging Research, 2024)
This paper studies the representation and conceptualization of aging people depending on the way they are referred to through a series of near synonyms: old / older / elderly / middle-aged / mature + N. A specific focus will be laid on the notions of "semantic preference," i.e., "the tendency for an item to co-occur with a set of semantically related words," and "semantic prosody," a.k.a. "evaluative, pragmatic, emotive or attitudinal prosody," to account for the evaluative aspect linked to certain denominations. This paper compares semantic preference and semantic prosody with five near-synonymous adjectives. It shows that denominations of aging people acquire a specific evaluation – a negative or positive semantic prosody – through their semantic preference, in that specific case the different attributive adjectives used in prenominal position of the sequences under scrutiny. This study addresses the question of the frequent negative axiology linked to the discourses on old age and aging through the notion of semantic prosody and will mostly examine the potential gender differences in the denominations of aging people.